Methodological Aspects of Predictive Mineragenic Studies Using Earth Remote Sensing Data - Petrov Vladislav; Ustinov Stepan; Minaev Vasilii (Russian Journal of Earth Sciences, 2025)
The article considers methodological aspects of allocation and substantiation of exploration areas for scarce types of ore minerals taking into account the concept of of mineral systems and using Earth remote sensing data with the application of geoinformation and neural network technologies using the example of the Argun metallogenic zone in South-Eastern Transbaikalia. Of the entire range of areas of fundamental and exploratory scientific research, the main attention within the framework of predictive and mineragenic studies is paid to solving the following problems: 1) allocation of lineaments (fault zones) based on processing of digital elevation models; 2) determination of hydraulically active fault structures for the period of ore formation based on tectonophysical reconstructions; 3) analysis of multispectral characteristics of pre-ore, ore-accompanying and post-ore metasomatites based on statistical processing of Landsat-8 satellite data; 4) assessment of fluid-dynamic settings of deposit formation based on data on the composition, properties and genesis of mineral-forming fluids. 5) creation of weight of evidence models based on statistical algorithms for processing data on the dynamics of ore-genetic processes. The feasibility of using such an approach for setting up predictive mineragenic studies on scarce types of strategic mineral raw materials in areas with complex climatic and landscape conditions is shown.